Alcohol Use Behaviors and Reasons to Abstain From or Limit Drinking Among Medically Vulnerable Youth. Issue 4 (July 2020) - Wisk, Lauren E.; Magane, Kara M.; Levy, Sharon; Weitzman, Elissa R.
Abstract : Background: Youth with chronic medical conditions (YCMC) use alcohol at levels similar to their healthy peers but face elevated risk for adverse health consequences. As salient reasons to abstain from or limit drinking (RALD) among YCMC are unknown, we sought to identify clusters of RALD and test associations with use behaviors. Methods: Eligible YCMC (ages 9–18) recruited from outpatient clinics reported their use behaviors and importance of potential RALD. Cluster analysis was used to discern RALD patterns, which were examined as predictors of alcohol use using multivariate regression. Results: Among 398 participants, 30.9% reported past year alcohol use. Concerns about impacts on medications, school, and disease status were the most frequently endorsed RALD; prior negative experiences with alcohol and family history were the least frequently endorsed. Five RALD clusters were identified for all YCMC and 2 for recent drinkers. Compared to the cluster with high endorsement of multiple general and health-related RALD, those predominantly citing concerns about addiction and those not strongly endorsing any RALD consistently reported greater alcohol use. Among recent drinkers, the cluster characterized by low concern across multiple RALD also consistently reported greater alcohol use compared to their counterparts expressing moderate concern. Conclusions: For YCMC, RALD are complex but endorsement of multiple general and health-related RALD is associated with less use, and health concerns are especially prevalent. More research is needed to understand how salient RALD can inform tailored interventions that aim to delay and reduce substance use and improve health outcomes for YCMC. Abstract : Supplemental Digital Content is available in the text